ผลของแก๊สไนโตรเจนในแก๊สปกคลุมอาร์กอนต่อโครงสร้างจุลภาคของรอยเชื่อมทิกพัลส์เหล็กกล้าไร้สนิมดูเพล็กซ์ที่มีส่วนผสมโครเมืยม 28 นิกเกิล 7 - ธารา ซงทัด (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The objective of this research was to study the effect of nitrogen in argon shielding gas (1-5 vol.%) on microstructure of 28Cr-7Ni-xN duplex stainless steel weldments. The nitrogen content of samples were 0.0018 wt.%(K1), 0.1100 wt.%(K2), 0.2300 wt.%(K3) and 0.3400 wt.%(K4). The conditions of TIG pulse welding were pulse currents of 140 A, base currents of 30 A, pulse frequency of 1.5 /s, welding speeds of 4.15 mm/s. The flow rate of shielding gas was 15 liters/min. Increasing of nitrogen in argon shielding gas resulted in increasing of austenite content of weld metal, fusion line and heat effect zone of all samples. The maximum amount of austenite content in weld metal, fusion line and heat effect zone was found in K3 sample, which had the maximum of nitrogen content in weld metal. From high to low nitrogen contents of weld metal the order can be as follow; K3 > K4 > K2 > K1. The increase of nitrogen content in argon shielding gas had also affected the Cr2N precipitation in weld metal, fusion line and heat effect zone. Precipitation of Cr2N in weld metal was found in sample K1 and K2, but it was not found in sample K3 and K4. Precipitation of Cr2N in fusion line in K2 was greater than in K4, K3 and K1, respectively. The amount of Cr2N precipitation in heat effect zone was found to be highest in K4 which was higher than in K3. However, a little precipitation of Cr2N in heat effect zone of K2 and K1 was also found.